Re-planning schedule and costs on the Balimed Denpasar hospital building development project - Eka Wahyuni; I Wayan Jawat; Ni Made Widya Pratiwi (Journal of Infrastructure Planning and Engineering, 2023)
In this study, a re-planning of schedules and costs will be carried out on the Balimed Denpasar Hospital Building Development Project which aims to be a basis for decision making so that the project runs according to plan. The calculation results obtained a Schedule Performance Index (SPI) of 0,683 and a Cost Performance Index (CPI) of 1 which shows that the project implementation was completed late with the budget as planned. If the project performance at the time of reporting remains the same until the rest of the work is completed, then the amount of the Estimate All Cost (EAC) is IDR. 46.881.134.933,39, which is the same amount as planned. This shows that there is no additional cost, so the total cost of remaining work is IDR. 40.249.362.635,43. The implementation time increased by 183 days because the Estimate All Schedule (EAS) was longer, which was 723 days from the original plan of 540 days.